EDUKASI DAN PELATIHAN PEMERIKSAAN INFEKSI SALURAN KEMIH (ISK) PADA SISWA SMK TEKNOLOGI LABORATORIUM MEDIS (TLM) DI KOTA BEKASI - Reza Anindita; Siti Nurfajriah; Ria Amelia; Noor Andryan Ilsan; Maulin Inggraini; Elfira Maya Sari (Universitas Mataram, 2023)
Urinary Tract Infection (UTI) is an infectious disease caused by bacterial colonization in the urinary tract. The bacteria most commonly found in UTI patients is E. coli. UTI is more common in women (79%) than men (21%) aged 17-35 years. The problem of UTIs causes an increase in morbidity (illness) rates, thereby increasing medical costs. Therefore, early prevention efforts are needed, one of which is through education and the introduction of UTI examinations through Community Service (PKM) activities for secondary school students. The aim of this PKM is to provide simple education and training regarding UTI examination for vocational school students majoring in TLM in Bekasi City. This PKM also provides students with experience in carrying out UTI examinations in the laboratory. This activity was carried out at the family partner STIKES with a total of 43 students majoring in TLM vocational schools. This activity stage includes planning, implementation and evaluation. Data analysis was carried out using descriptive and comparative tests for 2 samples using a paired t-test. The results of this activity showed that there were 37 (86.04%) female participants while there were 6 (13.95%) male participants. The average pre-test score was 3.48 while the post-test was 8.76 or an increase of 15.17%. The results of the paired t-test showed a significant difference between the pre-test and post-test with a significance value of (0.306<0.05). The conclusion of this PKM is that an evaluation using test instruments (pre test and post test) in the form of 10 multiple choice questions was able to significantly increase knowledge about UTI for 43 students of the TLM Department of Health Vocational Schools in Bekasi City.